Plan de negocios para la creación de un hostal en Quito - Pesántez Ramos, Karla Lissette (2016)
The following business plan details the creation of Uku Hostel. The target market for Uku Hostel will be young travelers between the ages of 18 and 35. The hostel will be based in the Mariscal area of Quito, due to the abundance of existing attractions for tourists in this area. The hostel is designed in line with the popular “Pod” style hostels, this style creates an attractive combination of both a welcoming homely feel which will be created by the, initially voluntary staff and surroundings, with a sense of security that does not come with a traditional dorm-room style design. The marketing plan is based on the „seven P‟s‟ method in order to create a clear and defined path to market for the hostel. Uku Hostel will have set prices of USD 25 for a shared room and USD 35 for a single room per person. The hostel will also incorporate a common room, laundry and dining areas, giving guests the opportunity to complete all of their necessary daily tasks within the hostel.